Digital Capabilities, Islamic Financial Literacy, and Halal Orientation Driving Online MSME Sustainability - Atikah Candraningtyas, Meiliza; Rahmawati, Yunaita (Inovasi Analisis Data, 2025)
Purpose: The purpose of this paper is to investigate how digital and Islamic strategic capacities are related to sustainability performance via the mediation of relational trust and financial inclusion. Method: A structural survey-based quantitative methodology with variance based structural equation model was used to test the direct and mediated relationships. Findings: From results, these strategic capabilities developed based on the foundation of digitalization and Islamic values do not contribute to sustainable performance automatically. Their success is contingent upon how well firms build online trust and adopt of inclusive digital financial services. Relation credibility re-enforces loyalty customers and operational stability, whereas digital financial inclusion improves transaction efficiency and financial resilience. Results indicate trust and financial inclusion as critical transmission mechanisms that help to spread the influence of organizational digital capability, Islamic financial literacy, halal orientation and digital marketing capability on long term sustainability performance. Novelty: This paper presents a dual-mediation framework where relational and institutional mechanisms are collectively regulated by the Resource-Based View (RBV) and Dynamic Capabilities Theory, applied to an Islamic digital business setting. Implications: The study contributes to theory by integrating fragmented capability–performance dynamics, and practitioners through advocating for the enhancing ethical digital strategies, trust-building process, and inclusive financial ecosystems for sustainable digital entrepreneurship.